Membangun Generasi Cerdas Melalui Rumah Belajar di Desa Pasar Melintang, Lubuk Pakam, Sumatera Utara - Ruth Mayasari Simanjuntak; Revol Alex Sibarani; Jois Febri Manik; Venti Br Ambarita; Khatarina Napitupulu (Jurnal Pengabdian Masyarakat Nusantara, 2025)
This Community Service Program aims to improve the quality of education in Pasar Melintang Village, Lubuk Pakam, North Sumatra, through the establishment of a Learning House. This initiative is designed to provide additional educational access for children and teenagers who face limitations in obtaining quality formal education. The program focuses on enhancing literacy and numeracy skills while providing academic support to help students better understand their school subjects. The methods used include an initial survey to identify educational needs, the implementation of structured learning activities, and the evaluation of the program's impact on student development. The results of the program show a significant improvement in reading and writing skills, as well as in understanding basic numeracy concepts. Additionally, this program contributes to raising community awareness about the importance of education. The presence of the Learning House is expected to have a long-term positive impact, preparing the younger generation in the village to face academic and social challenges in the future. Thus, this program not only provides direct benefits to the students but also creates a positive shift in the collective awareness of the community regarding the importance of education.